Comparison of early recovery and cognitive function after desflurane and sevoflurane anaesthesia in elderly patients: A meta-analysis of randomized controlled trials. (October 2015) - Chen, Gang; Zhou, Youfa; Shi, Qingyu; Zhou, Haiyan
Objectives: A meta-analysis to compare postoperative cognitive function and the time to specific recovery events in elderly patients (aged >65 years) anaesthetized with sevoflurane or desflurane. Methods: A systematic search of the PubMed®, Embase®, Cochrane Library and Chinese Biomedical databases was performed using the keywords 'sevoflurane' and 'desflurane'. Data and characteristics of appropriate randomized controlled trials (RCTs) were extracted. Results: The meta-analysis included five trials ( n  = 300). The time taken to follow commands (mean difference [MD] −3.27; 95% confidence intervals [CI] −4.95, −1.59), extubation (MD −1.59; 95%CI −2.62, −0.55), orientation (MD −4.31; 95%CI −4.99, −3.62), and recovery room discharge (MD −9.38; 95%CI −13.43, −5.42) were significantly shorter in the desflurane group than in the sevoflurane group. There was no significant between-drug difference in the incidence of postoperative cognitive dysfunction or the time taken to open the eyes. Conclusions: Desflurane is associated with a faster recovery from general anaesthesia than sevoflurane in elderly patients.